Health IT jumpstart the best first step toward an IT career in health information technology - Wilson, Patrick (Wiley, 2011)
IT professionals can learn how to launch a career in health information technology Government regulation is mandating that all physician practices, hospitals, labs, etc. move to electronic health records (EHR) by 2014, which, in turn, will create a demand for IT professionals to help medical facilities make this transition as smooth as possible. This book helps IT professionals make the move into health information technology (HIT) and shows you how EHRs can be securely created, maintained, distributed, and backed up under government regulations. The author duo is a pair of HIT expe.
Includes index. - Print version record
Keywords: Health services administration -- Information technology; Medical records -- Data processing; Medical informatics; Medical informatics -- Vocational guidance; Medicine -- Data processing; Medical Informatics; Medical Informatics Applications; Services de santé; Administration; Technologie de l'information; Dossiers médicaux; Informatique; Médecine; Informatique; Médecine; Informatique; Orientation professionnelle; Medicine; Data processing; Medical records; Data processing